Correction: Multi-scale microporous silica microcapsules from gas-in water-in oil emulsions. Issue 14 (27th March 2020) - Toprakcioglu, Zenon; Hakala, Tuuli A.; Levin, Aviad; Becker, Christian F. W.; Bernandes, Gonçalo J. L.; Knowles, Tuomas P. J.
Abstract : Correction for 'Multi-scale microporous silica microcapsules from gas-in water-in oil emulsions' by Zenon Toprakcioglu et al., Soft Matter, 2020, DOI: ; 10.1039/c9sm02274k .